Edward Herman and Manufacturing Consent in China - Yuezhi Zhao (Media Theory)
Boosted by a Chinese translation of Manufacturing Consent in 2011, â€œmanufacturing consentâ€ and â€œpropaganda modelâ€ have become fairly well-known terms in the Chinese communication studies field. Actual understandings and invocations of these ideas, however, are complex and multifaceted. Graduate students tend to have a superficial understanding of these ideas without a grasp of Herman and Chomskyâ€™s broader critique of the political economy of global communication. State propaganda officials and communication strategists tend to accept these concepts for their demystification of the US media system on the one hand, and use Manufacturing Consent as a â€œhow toâ€ guide to enhance the effectiveness of Chinese official communication on the other. While there are also examples of more substantive expositions of Herman and Chomskyâ€™s ideas on their own terms, a strong liberal perspective continues to take the US media as a normative model for China and ignore works such as Manufacturing Consent. As China expands its global reach, how Chinese scholars come to terms with Western critical communication scholarship and develop their own indigenous critique of the political economy of global communication has emerged as an issue of both theoretical and practical importance.